2013
DOI: 10.1142/s1084946713500088
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Competitive Attitudes of Entrepreneurs: Implications for Entrepreneurial Orientation at the Individual Level

Abstract: This study examined the competitive attitudes of entrepreneurs using the psychological theory of hyper-competitiveness versus personal development competitiveness in data from a cross-section of small business entrepreneurs. Results suggest most entrepreneurs view themselves, and their cohort, as personal development (e.g., growth oriented) competitors rather than as hypercompetitors (e.g., dominant individuals). The analysis suggests that, when applied at the individual level, the entrepreneurial orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
3
0
3
Order By: Relevance
“…If we look at the model by Covin and Slevin (1989), the current study adds one dimension to that model, autonomy, and if we look at the model by Lumpkin and Dess (1996), the current study excludes the “competitive aggressiveness” dimension. The dimension “competitive aggressiveness” has been deliberately excluded because, according to earlier research (André, 2013; Robinson and Stubberud, 2014), it is assumed that individuals compete against each other in a different way than firms do. If this were the case, there would be some bias in the responses, as it would be considered socially undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…If we look at the model by Covin and Slevin (1989), the current study adds one dimension to that model, autonomy, and if we look at the model by Lumpkin and Dess (1996), the current study excludes the “competitive aggressiveness” dimension. The dimension “competitive aggressiveness” has been deliberately excluded because, according to earlier research (André, 2013; Robinson and Stubberud, 2014), it is assumed that individuals compete against each other in a different way than firms do. If this were the case, there would be some bias in the responses, as it would be considered socially undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…We would assume kiasuism to relate positively with entrepreneurial intention as kiasuism was suggested to be a "highly competitive spirit" (Hwang et al, 2002, p. 75). However, a qualitative study conducted with entrepreneurs from United States found that the entrepreneurs are competitive, but the competitive attitude possessed by a majority of the entrepreneurs were grounded in personal development instead of wanting to be better than others (Andre, 2013). In Study 2b, we found the dimensions of kiasuism (getting ahead, pursuit of self-interest, not to lose out) to be associated with interpersonal competitiveness.…”
Section: Predictors Of Choice Goalmentioning
confidence: 66%
“…No que tange à vinculação institucional dos autores, houve predominância de contribuições brasileiras, com um total de sete trabalhos (Barbosa & Durante, 2013;Filardi, Barros & Fishman, 2014;Iizuka & Moraes, 2014;Rocha & Freitas, 2014;Silva, 2014;Souza & Silva, 2011;Zampier & Takahashi, 2011). Tiveram também cinco trabalhos norteamericanos (André, 2013;Chrysostome, 2010;Obschonka, Schmitt-Rodermund, Silbereisen, Gosling & Potter, 2013;Santandreu-Mascarell, Garzon & Knorr, 2013;Shane & Nicolaou, 2013), três artigos portugueses (Marques, Ferreira, Rodrigues & Ferreira, 2011;Zinga, Coelho & Carvalho, 2013), dois estudos alemães (Obschonka, Andersson, Silbereisen & Sverke, 2013;Obschonka, Silbereisen & Schmitt-Rodermund, 2012) e duas pesquisas da Malásia (Choe, Loo & Lau, 2013;Lope Pihie & Bagheri, 2011). Outros países contribuíram com apenas um estudo, como é o caso do Canadá (Mathieu & St-Jean, 2013), Chile (Sepulveda & Bonilla, 2011), Espanha (Arribas, Hernandez, Cirbano & Vila, 2012), Manda (Rezaei-Zadeh, Hogan, O 'Reilly, Cleary & Murphy, 2014) e Peru (Morales & Marquina, 2013) e a Polônia (Tyszka, Macko, Cieslik & Domurat, 2011).…”
Section: Empreendedorismo No Nível Individual: Análise De Preditoresunclassified
“…Existem ainda uma série de outras variáveis que foram consideradas nos modelos de investigação relacionados as características pessoais dos empreendedores, como: aspectos atitudinais (Choe et al, 2013;Lope Pihie & Bagheri, 2011), narcisismo (Mathieu & St-Jean, 2013), competitividade (André, 2013), comportamento anti-social leve (Obschonka, Andersson, et al, 2013), necessidade de realização e independência (Tyszka et al, 2011), competências empreendedoras (Santandreu-Mascarell et al, 2013 e comportamento pró-social (Arribas et al, 2012). Além disso, os trabalhos de revisão da literatura recente chamam atenção para o elevado número de características pessoais dos empreendedores relacionadas na literatura (Filardi et al, 2014) e a divergência entre as características elencadas pelos empreendedores como fundamentais para o sucesso do empreendimento e aquelas costumeiramente apontadas nos estudos empíricos (Rezaei-Zadeh et al, 2014).…”
Section: Síntese Das Evidências Empíricas E Antecedentesunclassified
See 1 more Smart Citation